Identification of surface NOx emission sources on a regional scale using OMI NO2. (January 2015) - Zyrichidou, I.; Κoukouli, M.E.; Balis, D.; Markakis, K.; Poupkou, A.; Katragkou, E.; Kioutsioukis, I.; Melas, D.; Boersma, K.F.; van Roozendael, M.
Abstract: In this study, an inverse modeling technique is applied to obtain, at a regional scale, top-down emission estimates for nitrogen oxides utilizing tropospheric nitrogen dioxide (NO2 ) columns retrieved by the OMI/Aura instrument and estimated by the Comprehensive Air Quality Model with extensions (CAM x ). The main idea, applied previously using models with coarse spatial resolution, is to combine the a priori information from the bottom up emission inventory used in an air quality simulation that covers the Balkan peninsula in a high resolution grid (0.1° × 0.1°) with the tropospheric NO2 quantities estimated for one complete year by CAM x and the tropospheric NO2 columns retrieved by satellite observations in order to identify missing emissions sources on a regional scale. The results have identified biases between the a priori and a posteriori emission inventories due to the missing emission sources or over-estimation of the spread and quantity of certain emission sources. In such a fine resolution grid we have also analyzed and considered the horizontal transport on the a posteriori NO x emissions. The deduced a posteriori NO x emissions, dominated by the fossil fuel emissions, were found to be1.11 ± 0.30 Tg N/y, compared to 0.87 ± 0.43 Tg N/y found in the a priori Balkan emission inventory. Soil emissions over the extended Greek domain, omitted in the a priori inventory, were estimated to account for almost 20% of the total emitted amount, while for the year 2009 the biomass burning NO x emission flux was also estimated and the average rate accounted for 0.5 × 10 −6  Tg N/km 2 . Highlights: The Balkan a posteriori NO x emissions inventory resulted in 1.11 Tg N/y. Fossil fuel NO x emissions over Greece comprise of the 80% of the total emissions. Soil emissions, omitted in a priori, accounted for 20% of the total over Greece. Microbial activity emissions are important in high resolution emission inventories. Biomass burning NO x emission rate, accounted for 0.5 × 10 −6  Tg N/km 2 over Greece.